Perceptions of NGOs employees of their framing in the Egyptian media - Ali, Ghadeer Ahmed (AUC Knowledge Fountain, 2020)
NGOs have been in Egypt since the 19th century; they had different nature, forms and activities throughout their history. In the past decade, attention to NGOs operating in Egypt has been increasing, especially after Jan. 2011 uprising and the changing political realities since then. The way media has been covering NGOs has been controversial, characterized by changing trends. This study seeks to understand and analyze the perceptions of employees of NGOs about their representation in the Egyptian media. The study will look at the image produced and how this image affected the existence and ability of NGOs to perform their activities through qualitative in-depth interviews. The interviews are conducted with 12 employees in health, educational, sustainable development and human rights, with experience in the NGO sector for not less than 4 years. The analysis showed that the framing of NGOs is affected by many factors including the relationship between NGOs and media, the relationship between the media and the state, and the relationship between NGOs and the state. The analysis of the interviews showed that the Egyptian media regularly frames the NGO sector with a negative image. This framing occurs regardless of the ownership type of the media outlet and the nature of the different organizations in the sector. It also showed that there are trends in the coverage of NGOs that are usually associated with the political landscape in Egypt. All these findings were associated with affecting the nature and the ability of NGOs operating in Egypt, some NGOs were closing down, some other had to work from outside the country, and others have their activities.